Penurunan Kadar Kromium Total Pada Limbah Elektroplating Menggunakan Adsorben Dari Daun Sukun (Artocarpus Altilis) Dengan Aliran Kontinu - Hardoyo Hardoyo; Nurbaiti Marsas Prilitasari; Natalina Natalina (TEKNIK, 2018)
The Electroplating wastewater the contain chromium (Cr) was one of hazardous waste to the environment. That waste have to treated before discharge to the environment.  One of the treatment of the Cr-containing wastewater was adsorption.  The leaf and stem of Artocarpus altilis  have potentially used as a adsorbent to treatment Cr-containing wastewater.  The process activated on the production of adsorbent could be done by acid and non acid process. The purpose of this research were to known the potential of Artocarpus altilis leaf to adsorpt the total-Cr in the electroplating wastewater.  The research was done using a 12cm length of 1,3 cm diameter of pipe reactor with up-flow continuously stream. The debit were used in this research was  0.255 cm3/det. The total-Cr were measured by Atomic Absorption Spectophotometer(AAS).  The research result show that the absorption using adsorbent that produced by acid process could be reduced total-Cr from 77.45 mg/l to 0.47mg/l (99.34%), while the absorption using adsorbent that  produced by non acid-process could be reduced total-Cr from 77.45mg/l to 4,75 mg/l (93,86%) only. The absorption using Artocarpus altilis leaf adsorbent that produced by acid-adsorbent could be used to treatment of Cr-containing electroplating wastewater, because  the treated-concentration from this process was lower than 0.5 mg/l (according on Quality standard PERMEN LH No 5, 2014.